Integrated nanozymes: facile preparation and biomedical applications - Wu, Jiangjiexing; Li, Sirong; Wei, Hui (Chemical communications (Cambridge, England), 2018)
Nanozymes have been viewed as the next generation of artificial enzymes due to their low cost, large specific surface area, and good robustness under extreme conditions. However, the moderate activity and limited selectivity of nanozymes have impeded their usage. To overcome these shortcomings, integrated nanozymes (INAzymes) have been developed by encapsulating two or more different biocatalysts ( e.g. , natural oxidases and peroxidase mimics) together within confined frameworks. On the one hand, with the assistance of natural enzymes, INAzymes are capable of specifically recognizing targets. On the other hand, nanoscale confinement brought about by integration significantly enhances the cascade reaction efficiency. In this Feature Article, we highlight the newly developed INAzymes, covering from synthetic strategies to versatile applications in biodetection and therapeutics. Moreover, it is predicted that INAzymes with superior activities, specificity, and stability will enrich the research of nanozymes and pave new ways in designing multifunctional nanozymes. Attributed to nanoscale proximity effects, integrated nanozymes with superior activities, specificity, and stability will be a hot topic in the future.